2022
DOI: 10.1289/ehp11519
|View full text |Cite
|
Sign up to set email alerts
|

Looking Forward: The Role of Academic Researchers in Building Sustainable Wastewater Surveillance Programs

Abstract: Background: In just over 2 years, tracking the COVID-19 pandemic through wastewater surveillance advanced from early reports of successful SARS-CoV-2 RNA detection in untreated wastewater to implementation of programs in at least 60 countries. Early wastewater monitoring efforts primarily originated in research laboratories and are now transitioning into more formal surveillance programs run in commercial and public health laboratories. A major challenge in this progression has been to simultaneou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…The cost of such a control system, for example, with adequate sensors, would be negligible compared to the amount of money already spent in this sector on the construction of conventional treatment plants, the pipes to carry wastewater to these points, and the construction of pumping stations, not to mention their maintenance [38].…”
Section: Connivance Of the Public Administrationsmentioning
confidence: 99%
“…The cost of such a control system, for example, with adequate sensors, would be negligible compared to the amount of money already spent in this sector on the construction of conventional treatment plants, the pipes to carry wastewater to these points, and the construction of pumping stations, not to mention their maintenance [38].…”
Section: Connivance Of the Public Administrationsmentioning
confidence: 99%
“…Wastewater data are not individual level data and cannot be stratified by age group, ethnic group, or many other variables, and it is not immediately clear what they can be realistically linked to. To interpret wastewater data appropriately and meaningfully, they must be validated against infection and disease data to establish how changes in signals in wastewater could be linked to the circulation of pathogens 2728…”
Section: Surveillancementioning
confidence: 99%
“…However, there is still uncertainty about how to appropriately interpret WBE data and use it to aid public health decision-making [18][19][20]. Accurately interpreting SARS-CoV-2 RNA concentrations as increasing, decreasing, or plateauing is important for guiding pandemic response efforts.…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing time-series data for trends, a large number of observations provides greater statistical power [24], and high frequency (e.g., daily) data has previously been identified as ideal for WBE to most accurately identify trends [25]. However, daily sampling and processing of wastewater can be challenging to implement [18,20], and many facilities across the United States only collect samples once per week [26,27]. Previous studies found that sampling wastewater at least twice per week is needed to detect correlations between wastewater SARS-CoV-2 RNA concentrations and incident clinical cases [6,28,29], but these studies collected data over a limited duration of time (at most six months) or did not include daily data in the analysis.…”
Section: Introductionmentioning
confidence: 99%